MENINGKATKAN BUDAYA MENABUNG REMAJA USIA SEKOLAH MELALUI LITERASI KEUANGAN DAN APLIKASI MENABUNG - Munir, Sirojul (Indonesian Community Service and Empowerment Journal (IComSE), 2024)
The level of financial literacy among teenagers tends to be low; nationally, the 2022 Financial Services Authority (OJK) survey results showed that the financial literacy index of the Indonesian people is still below 50%. Financial literacy is a personal ability to make decisions based on knowledge and skills to manage financial resources effectively to achieve financial well-being. The school digitalization program, which applies information and communication technology (ICT), is expected to improve education services in the learning system, curriculum, and administration. This community service activity aims to conduct training and socialization of financial literacy to foster character formation in students through learning to live frugally with a savings program at school by providing a savings application platform at SMP PGRI 10 Jakarta.